(untitled) (Bangladesh Journal of Botany, 2021)
The biological activities of Bistorta amplexicaulis (D.Don) Greene rhizome and leaves extracts were evaluated. In vitro antibacterial activity, direct bioautography, and spot screening of TLC developed bands were investigated against seven bacterial pathogens. Screening of phytochemical constituents was also done through both qualitative and thin layer chromatographic methods. DMSO extracts of rhizome indicated high sensitivity (12.33 ± 1.52 and 11.33 ± 0.57 mm) against Escherichia coli. Whereas methanolic and acetonic extracts of rhizome indicated significant inhibition (11.66 ± 1.15 and 11.33 ± 0.57 mm) of S. marcesscens. All leaf extracts revealed low sensitivity against E. coli. TLC-bioautography and spot screening methods showed the significant use of B. amplexicaulis as an antibacterial agent. Antioxidant activity indicated that acetone and DMSO extracts of rhizome and methanolic leaf extract have maximum scavenging potential. Among the screened phytochemicals, terpenoids, phenols, and quinones were detected in all extracts indicating the potential use of B. amplexicaulis as both antibacterial and antioxidant agents. Bangladesh J. Bot. 50(3): 613-622, 2021 (September)